Diet-Morphology Correlations in the Radiation of South American Geophagine Cichlids (Perciformes: Cichlidae: Cichlinae) - López-Fernández, Hernán; Winemiller, Kirk O.; Montaña, Carmen; Honeycutt, Rodney L. (PLOS ONE, 2012)
Genera within the South American cichlid tribe Geophagini display specialized feeding and reproductive strategies, with some taxa specialized for both substrate-sifting and mouth brooding. Several lineages within the clade also possess an epibranchial lobe (EBL), a unique pharyngeal structure that has been proposed to have a function in feeding and/or mouth brooding. A recently published genus-level phylogeny of Neotropical cichlids was used as the evolutionary framework for investigating the evolution of morphological features presumably correlated with diet and mouth brooding in the tribe Geophagini. We tested for possible associations between the geophagine epibranchial lobe and benthic feeding and mouth brooding. We also addressed whether the EBL may be associated with unique patterns of diversification in certain geophagine clades. Tests of binary character correlations revealed the EBL was significantly associated with mouth brooding. We also tested for a relationship between diet and morphology. We analyzed stomach contents and morphometric variation among 21 species, with data for two additional species obtained from the literature. Principal Components Analysis revealed axes of morphological variation significantly correlated with piscivory and benthivory, and both morphology and diet were significantly associated with phylogeny. These results suggest that the EBL could be an adaptation for either feeding or mouth brooding. The EBL, however, was not associated with species richness or accelerated rates of phyletic diversification.